Drivers of Developing Asia's Growth: Past and Future - Donghyun Park; Jungsoo Park (Asian Development Bank (ADB), 2010)
While developing Asia has recovered strongly from the global crisis, the region faces the medium- and long-term challenge of sustaining growth beyond the crisis. The central objective of this paper is to empirically investigate the sources of economic growth in 12 developing Asian economies during 1992-2007 via a two-stage analysis. In the first stage, we estimate total factor productivity growth (TFPG) and account for the relative importance of labor, capital, and TFPG in growth. In the second stage, we examine the effect of fundamental determinants of growth such as human capital on both economic growth and TFPG. Our most significant finding is that TFPG is becoming relatively more important as a source of developing Asia's growth. Our results also confirm the relevance of supply-side factors, in particular human capital and openness to trade, for developing Asia's medium- and long-term growth. The overarching implication for policy makers is that supply-side policies that foster productivity growth will be vital for sustaining developing Asia's future growth in the postcrisis period
hdl:11540/4181
Keywords: O40; O47; 330; Growth; total factor productivity; factor accumulation; growth accounting; determinants of growth; panel data; Asia; Wirtschaftswachstum; Produktivität; Entwicklungsländer; Asien